Is Mother’s Education Important for Preventing Stunting?: A Systematic Review - Sri Rahmi Putri Mawardi; Azrimaidaliza Azrimaidaliza; Idral Purnakarya (GLOBAL HEALTH SCIENCE GROUP, 2026)
Stunting is a condition of growth failure in children under five caused by chronic malnutrition that occurs over a long period, characterized by a z-score value of less than -2 standard deviations. The global prevalence of stunting among children under five in 2024 was 23.2%. This study aims to collect evidence from published articles regarding the relationship between maternal education and the risk of stunting. This study employed a systematic review method following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Article searches were conducted using three databases: ScienceDirect, MDPI, and PubMed. The inclusion criteria for this study were articles published between 2021 and 2025, while the exclusion criteria were duplicate articles, those without full text, those with irrelevant titles or abstracts, and systematic reviews. A total of 827 articles were identified, 16 articles were reviewed (2 from ScienceDirect, 1 from MDPI, 13 from Pubmed), consisting of 14 cross-sectional studies and 2 cohort studies. The review found that almost all studies demonstrated a significant association between maternal education and stunting incidence. These findings were consistent across various countries, including Indonesia, Ethiopia, China, Uganda, Iran, Bangladesh, and several regions in Africa. Maternal education has been proven to be associated with the risk of stunting among children under five. The lower the mother’s level of education, the higher the risk of stunting; conversely, higher maternal education is associated with a lower risk of stunting. Several countries have implemented both health and non-health sector programs to prevent stunting. In Brazil, initiatives to improve women’s access to education have successfully reduced stunting prevalence, whereas such programs have not yet been implemented in Indonesia.